2023
DOI: 10.1371/journal.pone.0280757
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to nurse practitioner implementation of medication abortion in Canada: A qualitative study

Abstract: In this study we explored nurse practitioner-provided medication abortion in Canada and identified barriers and enablers to uptake and implementation. Between 2020–2021, we conducted 43 semi-structured interviews with 20 healthcare stakeholders and 23 nurse practitioners who both provided and did not provide medication abortion. Data were analyzed using interpretive description. We identified five overarching themes: 1) Access and use of ultrasound for gestational dating; 2) Advertising and anonymity of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Providers of abortion at all gestations have been found to face many challenges in their role, including grappling with the ethical considerations of their work, and at times experiencing negative emotional impacts, such as anxiety, sadness and grief [ 17 20 ]. Many have described having inadequate supports in place to manage these challenges [ 17 , 20 , 21 ]. Though providers in this study similarly found their work difficult at times, they highlighted that the supportive team environment enabled them to successfully navigate emotional and ethical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Providers of abortion at all gestations have been found to face many challenges in their role, including grappling with the ethical considerations of their work, and at times experiencing negative emotional impacts, such as anxiety, sadness and grief [ 17 20 ]. Many have described having inadequate supports in place to manage these challenges [ 17 , 20 , 21 ]. Though providers in this study similarly found their work difficult at times, they highlighted that the supportive team environment enabled them to successfully navigate emotional and ethical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, post-discharge, these nursing interventions are often disrupted, resulting in ineffective engagement with the patient’s behavior. [ 5 , 6 ] Continuous precision nursing, as a form of post-discharge continuity of care, has shown positive effects in sustaining treatment efficacy and enhancing patient compliance across various clinical departments. [ 7 , 8 ] Nevertheless, there is limited research on its application in threatened miscarriage.…”
Section: Introductionmentioning
confidence: 99%